Moslem Millennials Donor Intention Through Donation-Based Crowdfunding in Indonesia - Moh. Helmy Najih Ramadhan; Achsania Hendratmi (Jurnal Ekonomi Syariah Teori dan Terapan, 2023)
ABSTRACT: The existence of donation-based crowdfunding as an alternative fundraising system in Indonesia has a great opportunity to keep growing. The millennials as a digitally-native generation should actively contribute to the development of donation-based crowdfunding. This study tries to identify the effect of the variables of performance expectancy, effort expectancy, social influence, facilitating conditions, sense of trust, and experience expectation on the intention to donate donation-based crowdfunding by the Muslim millennials in Indonesia. Respondents who were analyzed were 156 people who were selected using purposive sampling and tested using SmartPLS. The results showed that Social Influence, Sense of Trust, and Experience Expectation had a positive influence on Intention to donate to donation-based crowdfunding. However, a test of Performance Expectancy, Effort Expectancy, and Facilitating Conditions shows that there are different findings. The data presented in this study is expected to add new perspectives for relevant stakeholders to develop donation-based crowdfunding in Indonesia. Keywords: Donation-based Crowdfunding, Moslem Millennials, Partial Least Square, Donation.   ABSTRAK: Kehadiran donation-based crowdfunding sebagai alternatif sistem penggalangan dana di Indonesia memiliki peluang yang besar untuk terus berkembang. Generasi milenial sebagai generasi yang terbiasa dengan teknologi seyogyanya berperan aktif dalam perkembangan platform donation-based crowdfunding. Penelitian ini bertujuan untuk mengidentifikasi pengaruh variabel performance expectancy, effort expectancy, social influence, facilitating conditions, sense of trust serta experience expectation terhadap intention to donate to donation-based crowdfunding dari para generasi milenial muslim di Indonesia. Responden yang dianalisis sejumlah 156 orang yang dipilih menggunakan teknik purposive sampling serta diuji menggunakan SmartPLS. Hasil penelitian menunjukkan Social Influence, Sense of Trust, dan Experience Expectation memiliki pengaruh positif terhadap Intention to donate to donation-based crowdfunding. Namun, pengujian pada Performance Expectancy, Effort Expectancy, dan Facilitating Conditions menunjukkan hasil yang berbeda. Data yang ditampilkan dalam penelitian ini diharapkan menambah sudut pandang baru bagi stakeholder terkait agar dapat mengembangkan donation-based crowdfunding di Indonesia. Kata Kunci: Donation-based Crowdfunding, Generasi Milenial Muslim, Partial Least Square, Donasi.   DAFTAR PUSTAKA Achmad, R. W., Poluakan, M. V., Dikayuana, D., Wibowo, H., & Raharjo, S. T. (2019). Potret generasi milenial pada era revolusi industri 4.0. Focus: Jurnal Pekerjaan Sosial, 2(2), 187-197. doi:10.24198/focus.v2i2.26241 Ajzen, I. (1991). The theory of planned behavior. Organizational Behavior and Human Decision Processes, 50, 179-211. doi:10.1016/0749-5978(91)90020-t Ardiansyah, D. O. (2016). Pengaruh komunikasi terhadap kinerja karyawan dengan dimediasi oleh kepuasan kerja (Studi pada bagian produksi pabrik kertas pt. setia kawan makmur sejahtera tulungagung). Jurnal Bisnis dan Manajemen, 3(1), 16-30. doi:10.26905/jbm.v3i1.70 Asosiasi Penyelenggara Jasa Internet Indonesia. 2020. Laporan Survei Internet APJII 2019 – 2020 (Q2). Jakarta: Asosiasi Penyelenggara Jasa Internet Indonesia. Az-Zuhaili, Wahbah. (2011). Fiqih Islam Wa Adillatuhu (Vol. 3). Jakarta: Gema Insani. Baptista, G., & Oliveira, T. (2015). Understanding mobile banking: The unified theory of acceptance and use of technology combined with cultural moderators. Computers in Human Behavior, 50, 418-430. doi:10.1016/j.chb.2015.04.024 Bekkers, R. (2003). Trust, accreditation, and philanthropy in the Netherlands. Nonprofit and Voluntary Sector Quarterly, 32(4), 596–615. doi:10.1177/0899764003258102 Belleflamme, P., Lambert, T., & Schwienbacher, A. (2013). Crowdfunding: Tapping the right crowd. Journal of Business Venturing, 29(5), 585–609. doi:10.1016/j.jbusvent.2013.07.003 Bhawika, G. W. (2017). Risiko dehumanisasi pada crowdfunding sebagai akses pendanaan berbasis teknologi di Indonesia. Jurnal Sosial Humaniora, 10(1), 47-58. doi:10.12962/j24433527.v10i1.2355 Choy, K., & Schlagwein, D. (2015). IT affordances and donor motivations in charitable crowdfunding: The "Earthship kapita" case. ECIS 2015 Completed Research Papers. 31. Diakses dari https://aisel.aisnet.org/ecis2015_cr/31 Fahrullah, A., Anwar, M. K., Ridlwan, A. A., Prabowo, P. S., & Yasin, A. (2020). How Ramadan and global pandemic affect religiosity and donating behaviors. Shirkah: Journal of Economics and Business, 5(2), 250. doi:10.22515/shirkah.v5i2.323 Falcone, R., & Castelfranchi, C. (2001). Social trust: A cognitive approach. Trust and Deception in Virtual Societies, 55–90. doi:10.1007/978-94-017-3614-5_3 Fuadi, N. F., Farida, D. N., & Saadah, N. (2020). Empathy or self-credibility? An empirical study of intentions to donate through social crowdfunding using the UTAUT model. Proceedings of the 1st Conference on Islamic Finance and Technology, CIFET, 21 September, Sidoarjo, East Java, Indonesia. doi:10.4108/eai.21-9-2019.2293953 Gerber, E. M., Hui, J. S., & Kuo, P. Y. (2012). Crowdfunding: Why people are motivated to post and fund projects on crowdfunding platforms. Retrieved from https://www.researchgate.net/publication/261359489 Ghozali, I. (2021). Partial Least Squares: Konsep, Teknik dan Aplikasi Menggunakan Program SmartPLS 3.2.9 untuk Penelitian Empiris Jilid 3. Semarang: Badan Penerbit Universitas Diponegoro. Gopay. (2020). Gopay Digital Donation Outlook 2020. Hidayatullah, S., Waris, A., Devianti, R. C., Sari, S. R., Wibowo, I. A., & Made, P. (2018). Perilaku generasi milenial dalam menggunakan aplikasi go-food. Jurnal Manajemen dan Kewirausahaan, 6(2), 240-249. doi:10.26905/jmdk.v6i2.2560 Hossain, M., & Oparaocha, G. O. (2017). Crowdfunding: Motives, definitions, typology and ethical challenges. Entrepreneurship Research Journal, 7(2). doi:10.1515/erj-2015-0045 Kementerian Pemberdayaan Perempuan dan Perlindungan Anak. (2018). Statistik Gender Tematik: Profil Generasi Milenial Indonesia. Jakarta: Kementerian Pemberdayaan Perempuan dan Perlindungan Anak. Kholid, M. N. (2019). Determinants of intention to use Islamic mobile banking: Evidence from millennial generation. Jurnal Ekonomi & Keuangan Islam, 5(2), 53-62. doi:10.20885/jeki.vol5.iss2.art2 Kitabisa.com. (2018). Online Giving Report 2018: Insights for Nonprofits and Brands. Li, Y., He, T., Song, Y., Yang, Z., & Zhou, R. (2017). Factors impacting donors intention to donate to charitable crowd-funding projects in China: A UTAUT-based model. Information, Communication & Society, 21(3), 404-415. doi:10.1080/1369118x.2017.1282530 Li, B., Hou, F., Guan, Z., & Chong, A. (2019). How social experience encourages donation intention to charitable crowdfunding projects on social media: Empathy and personal impulsiveness. PACIS 2019 Proceedings, 195. Diakses dari https://aisel.aisnet.org/pacis2019/195 Moon, Y., & Hwang, J. (2018). Crowdfunding as an alternative means for funding sustainable appropriate technology: Acceptance determinants of backers. Sustainability, 10(5), 1456. doi:10.3390/su10051456 National Chamber Foundation. (2012). The Millennial Generation Research Review. Washington DC: National Chamber Foundation. Pangaribuan, C. H., & Wulandar, Y. S. (2019). A crowdfunding platform user acceptance: An empirical examination of performance expectancy, effort expectancy, social factors, facilitating condition, attitude, and behavioral intention. Proceedings of the 1st Sampoerna University-AFBE International Conference, SU-AFBE 2018, 6-7 December 2018, Jakarta Indonesia. doi:10.4108/eai.6-12-2018.2286301 Purnamasari, D. (2018). Riset Mandiri: Generasi Milenial Suka Memberi Sumbangan. Retrieved from https://tirto.id/generasi-milenial-suka-memberi-sumbangan-cLHu Putra, Y. S. (2016). Theoritical review: Teori perbedaan generasi. Among Makarti, 9(2). doi:10.52353/ama.v9i2.142 Rondan-Cataluña, F. J., Arenas-Gaitán, J., & Ramírez-Correa, P. E. (2015). A comparison of the different versions of popular technology acceptance models. Kybernetes, 44(5), 788–805. doi:10.1108/k-09-2014-0184 Taiwo, A. A., & Downe, A. G. (2013). The theory of user acceptance and use of technology (UTAUT): A meta-analytic review of empirical findings. Journal of Theoretical and Applied Information Technology, 49(1), 48-58. Diakses dari http://www.jatit.org/volumes/Vol49No1/7Vol49No1.pdf Tirdanatan, N. U., Georgiana, V., Sun, Y. (2014). Evaluasi good corporate governance atas kebutuhan donatur pada penerapan crowdfunding di Indonesia: Studi kuantitatif dan kualitatif pada efekrumahkaca.net, Patungan.Net, dan Wujudkan.Com. ComTech, 5(1), 123-135. doi:10.21512/comtech.v5i1.2598 Venkatesh, V., Morris, M. G., Davis, G. B., & Davis, F. D. (2003). User acceptance of information technology: Toward a unified view. MIS Quarterly, 8, 425–478. doi:10.2307/30036540 Walgito, B. (1981). Pengantar Psikologi Umum. Yogyakarta: Andi Offset. Wheat, R. E., Wang, Y., Byrnes, J. E., & Ranganathan, J. (2013). Raising money for scientific research through crowdfunding. Trends in Ecology & Evolution, 28(2), 71–72. doi:10.1016/j.tree.2012.11.001 Wisesa, A. D., Kholid, M. N., & Hamdani, R. (2019). Factors influencing intention to donate through donation crowd-funding: Evidence from Indonesia. Society of Interdisciplinary Business Research, 8(5). doi:10.2139/ssrn.3784229